Ultrasonic plastic deformation of steels; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Zaitsev K. V. Konstantin Viktorovich; Klimenov V. A. Vasily Aleksandrovich; Loshchilova M. A. Marina Andreevna; Polovnikov C. (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen